EFEKTIVITAS PELAKSANAAN BIMBINGAN MANASIK HAJI PADA KUA KECAMATAN DI KOTA PADANG - Rasyidul Basri (Harmoni, 2015)
This research applies survey and descriptive method with quantitative and qualitative approach. This research aims to figure out the effectiveness, supporting and inhibiting factors in conducting Hajj Manasik guidance at sub-District Religous Affair Office in Padang in 2014. The sample is 100 of 929 participants from 10 sub-District Religious Affair Offices consisting of head of sub-District Religious Affair Office/ committee, head of Hajj and Umrah department, head of Padang Religious Affairs Office and Hajj participants.The results shows that the guidance Hajj Manasik implementation 2014 in Padang City is effective in manager level while management, programs, and infrastructure need to be developed. It can be seen on the achievements of the management indicator: 75.55% manager indicator, 71.72% management indicator, 67.85% program indicator, and 69.43% infrastructure indicator. Recommendation is for General Director of Hajj and Umrah through West Sumatera Religious Affairs Office to issue the latest Religious Minister decree containing sub-District Religious Affair Office`s tasks as a Hajj consultant at sub-district level and give a service on marriage and reconciliation.